2015
DOI: 10.1097/sap.0b013e318298e6f5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fat Particle-to-SVF Ratio on Graft Survival Rates in Rabbits

Abstract: It was suggested that the optimal fat particle-to-SVF ratio might be 3:1, with a low resorption rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Five studies were identified, in which immunocompetent animals were used of which two used rodents (allogeneic cells) [ 16 , 50 ] and the remaining studies used rabbits (autologous cells) [ 17 , 51 , 52 ]. The relative survival improvement for CAL ranged from 1.29- to 4.14-fold compared with their respective control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies were identified, in which immunocompetent animals were used of which two used rodents (allogeneic cells) [ 16 , 50 ] and the remaining studies used rabbits (autologous cells) [ 17 , 51 , 52 ]. The relative survival improvement for CAL ranged from 1.29- to 4.14-fold compared with their respective control group.…”
Section: Resultsmentioning
confidence: 99%
“…Ni et al performed a study that compared four different fat tissue to SVF ratios in an immunocompetent rabbit model [ 52 ]. They used a total of 0.8 g with varying ratios between fat and SVF.…”
Section: Resultsmentioning
confidence: 99%
“…The search of publications completed for the current study yielded 15 murine ( Table I ) ( 48 , 52 , 57 69 ) and 19 human ( Table II ) ( 30 , 53 55 , 70 84 ) studies that assessed the effect of fat graft enrichment with freshly isolated ADSCs (SVF) or ex vivo cultured ADSCs. A total of 24 of the studies compared SVF assisted lipotransfer to traditional lipotransfer (control), 10 compared ex vivo expanded ADSC-enriched fat grafting to controls and one animal study compared both.…”
Section: Experimental and Clinical Trials With Adsc-assisted Fat Grafmentioning
confidence: 99%
“…Part of the lipoaspirate was used to extract the SVF, which was either used directly as a source of ADSCs or used for ex vivo expansion of the ADSCs. The majority of animal studies (n=11) investigated immunosuppressed mice (severe combined immunodeficiency (SCID) or nude mice) and only three investigated rabbits ( 59 , 60 , 69 ). Nude mice are the most commonly used murine model for xenografting.…”
Section: Experimental and Clinical Trials With Adsc-assisted Fat Grafmentioning
confidence: 99%
See 1 more Smart Citation